Exploring the Links Between Self-Compassion, Body Dissatisfaction, and Acceptance of Cosmetic Surgery in Young Italian Women - Nerini, Amanda; Matera, Camilla; Di Gesto, Cristian; Policardo, Giulia Rosa; Stefanile, Cristina (Frontiers in Psychology, 2019)
This study aimed to examine the association between positive (self-kindness, common humanity, and mindfulness) and negative (isolation, self-judgment, and over-identification) components of self-compassion, and both body dissatisfaction and acceptance of cosmetic surgery among women, through the mediation (for the negative components) of internalization and physical appearance comparison. The participants were 220 young Italian women aged 19–31 (M = 21) years, who completed a questionnaire assessing the variables of interest. Path analysis indicated that higher mindfulness was directly linked to lower acceptance of cosmetic surgery. Mindfulness presented the strongest link with cosmetic surgery, as it was directly associated with acceptance of cosmetic surgery for both social and interpersonal motivations and with consideration of undergoing some cosmetic procedures. Common humanity and self-kindness were related to acceptance of cosmetic surgery for social reasons. Over-identification seemed to be associated with body dissatisfaction and acceptance of cosmetic surgery both directly and indirectly through internalization and physical appearance comparison. Self-judgment and isolation did not present a significant association with either body dissatisfaction or acceptance of cosmetic surgery. These findings confirm that psychological assessment of women who are interested in cosmetic surgery is highly recommended. Interventions should not consider self-compassion as a whole, but they should rather focus on some of its components. The role of over-identification seems to be especially pivotal, as higher scores on this dimension are linked to higher levels of body dissatisfaction and greater acceptance of cosmetic surgery.